Conjunctival Melanoma With Morphologic Diversity and Orbital Invasion. (May 2016) - Zoroquiain, Pablo; Nayman, Taylor; Fernandes, Bruno; Burnier, Miguel N.
Abstract : Abstract: A 68-year-old male with a previous history of 3 dysplastic skin nevi was referred to ophthalmology for a 1-year history of a progressive growth of a firm nodule in the lower left eyelid. Examination revealed a firm nodule in the inferior anterior orbit and mild conjunctival pigmentation on the left inferior fornix. A conjunctival incisional biopsy was taken, showing a melanoma. Because of the infiltration by the mass of the orbit on magnetic resonance imaging, an exenteration was performed. Histopathological analysis showed a unique conjunctival melanoma showing morphological diversity; specifically, a pattern characteristic of conjunctival melanoma, and the concurrent presence of staghorn patterns, signet-ring cells, and rosettoid patterns. Seven years of follow-up shows that the patient is alive with no further metastasis or recurrence. This report represents the first documented case of multiple morphologic patterns within a conjunctival melanoma.